2022
DOI: 10.1039/d2fo01102f
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid is associated with the attenuation of dysfunctions of mesenchymal stem cells in the abdominal aortic aneurysm wall

Abstract: The distribution of eicosapentaenoic acid-containing phosphatidylcholine was similar to that of mesenchymal stem cells markers in the abdominal aortic aneurysm wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, studies of the distribution of EPA in the human aortic wall is very limited. We have previously reported that the distribution of EPA-PC in human AAA walls is similar to that of MSCsmarker positive cells and M2 macrophage-marker positive cells 14,15) . On the other hand, the distribution of EPA-PC is not similar to that of M1 macrophage-marker positive cells 15) .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, studies of the distribution of EPA in the human aortic wall is very limited. We have previously reported that the distribution of EPA-PC in human AAA walls is similar to that of MSCsmarker positive cells and M2 macrophage-marker positive cells 14,15) . On the other hand, the distribution of EPA-PC is not similar to that of M1 macrophage-marker positive cells 15) .…”
Section: Discussionmentioning
confidence: 56%
“…In other words, diets containing less EPA have fewer protective effects against AAA. In EPA-rich diets, the distribution of EPA-PC is similar to that of both MSC-positive markers and M2 macrophages in the aortic wall of AAA model rats 13,14) . Similarity in the distribution between EPA-PC and M1 macrophages in the aortic wall has not been clearly observed 13) .…”
Section: Discussionmentioning
confidence: 72%
“…This finding is consistent with Ezure and Amano who saw no difference in either cell abundance or ColIa1 expression compared to control as a function of EPA [31] . These data suggest that even though EPA may have anti-inflammatory effects in the cardiovascular system [32] , [33] , [34] and in patients with cancer [35] , the effect of EPA on the musculoskeletal system is less clear [36] , [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Low serum EPA levels and EPA/AA ratio were associated with the size and growth rate of AAA [121]. The protective effects and underlying mechanisms of EPA in AAA have been identified (Figure 4): (1) increased anti-inflammatory property of macrophages due to lessened inflammatory factor such as MMP2 and MMP9 levels [122][123][124] (2) attenuated of mesenchymal stem cell (MSC) dysfunctions [125] (3) suppressed the weakening of the vascular wall by inhibiting the elastin fiber degradation caused by nicotine [126] (4) inhibition of endothelial cell-mediated inflammatory factors [107]. AAA is associated with inflammation and oxidative stress, the latter of which contributes to activation of macrophages, a prominent cell type in AAA.…”
Section: Omega -3 Polyunsaturated Fatty Acidmentioning
confidence: 99%